Open Access Repositories & Scholarly Publication - Johnson, Gareth J (2006)
This presentation briefly covers some of the issues around Open Access as it pertains to institutional repositories in the UK higher educational sector. It includes an overview of the current activities of SHERPA, along with the benefits, concerns and potential resolutions of issues in the open access sector. Some speculation as to future trends and developments in scholarly publishing and open access is included.